PERKEMBANGAN LEMBAGA KEUANGAN MIKRO SYARIAH DI TENGAH PERSAINGAN LEMBAGA KEUANGAN SYARIAH BANK DAN NON BANK (Studi kasus (KSPPS) BMT Assyafi'iyah Berkah Nasional Cabang kota Metro ) - Maulana Syarif Afwa; Sulistyowati (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The establishment of sharia microfinance institutions, one of which is KSPPS BMT Assyafi'iyah Berkah Nasional, as a sharia microfinance institution, clearly has great significance for sharia-oriented economic development. BMT Assyafi'iyah took several steps in order to stand out from its competitors, one of which was selecting staff who might be qualified in their field. By utilizing the Ceria digital application, BMT Assyafi'iyah implemented a plan in an effort to increase consumer confidence in the form of savings. Literature review Descriptive methodology is used in the descriptive and qualitative analysis of this study to describe real-world situations. data sources found in academic journals.